2015
DOI: 10.1021/acs.jpcc.5b01769
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Coordination in Cyclic-Carbonate-Based Gel Polymer Electrolyte

Abstract: A gel polymer electrolyte based on a polymer host comprising cyclic carbonate and ethylene oxide (EO) moieties in the side chains and the liquid electrolyte 1 M LiPF 6 in ethylene carbonate (EC):dimethyl carbonate (DMC) 1:1 is studied regarding ionic and intermolecular interactions. Raman and NMR spectroscopic studies reveal that apart from the solvents of the liquid electrolyte also the polymer host is interacting with lithium ions. However, these interactions seem to be limited to the EO side chains. No evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In addition, Tillmann et al produced a gel polymer electrolyte based on a polymer host containing cyclic carbonate and ethylene oxide moieties in the side chains. This gel polymer electrolyte was found to be promising for utilization in lithium‐ion batteries as it displays a high ionic conductivity at 2.3 mS cm −1 and a stable performance in graphite full cells . Two groups of low‐volatility plasticizers were synthesized by Liang et al, both of which were composed of highly polar cyclic carbonate and more flexible short ethylene oxide chains.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Tillmann et al produced a gel polymer electrolyte based on a polymer host containing cyclic carbonate and ethylene oxide moieties in the side chains. This gel polymer electrolyte was found to be promising for utilization in lithium‐ion batteries as it displays a high ionic conductivity at 2.3 mS cm −1 and a stable performance in graphite full cells . Two groups of low‐volatility plasticizers were synthesized by Liang et al, both of which were composed of highly polar cyclic carbonate and more flexible short ethylene oxide chains.…”
Section: Applicationsmentioning
confidence: 99%
“…Crosslinked micelles demonstrated enhanced stability against extensive dilution with aqueous solvents and in the presence of physiological simulating serum concentration. [104] Additionally, Yan et al [105] prepared a functionalized six-membered cyclic carbonate monomer containing a protected thiol group, MTC, and DOX was loaded into the Poly(LLA-co-acryloyl carbonate) Ligament tissue engineering [106] PLMC Bone tissue engineering [107] Poly(LLA-co-PC) Bone tissue engineering [134] Allyl-functional poly(carbonate) Scaffold tissue engineering [135] LLA-co-TMC Vascular tissue engineering [108] PPC/grafted tetracalcium phosphate (g-TTCP) Cartilage tissue engineering [136] OligoTMC-PEG-oligoTMC Cartilage tissue engineering [137] PLLA-TMC-glycolide Cardiovascular tissue engineering [138] Carbonate free polymer electrolyte Electrolytes [139] Trifluoropropylene carbonate Electrolytes [140] 4-(Trimethylsilyl)-1,3-dioxolan-2-one Electrolytes [141] Poly(ether 1,2-glycerol carbonate)s Electrolytes [142] Carbonate derivatives Electrolytes [143] Ethylene carbonate Electrolytes [144] Propylene carbonate Electrolytes [145] PTMC Electrolytes [146] Propylene carbonate Electrolytes [147] Vinyl ethylene carbonate Thermosetting coatings [148] α,ω-Dihydroxyl poly(limonene carbonate)s Thermosetting coatings [149] α,ω-Dihydroxy-terminated PCs Thermosetting coatings [150] Furfuryl cyclocarbonate ether Thermosetting coatings [151] PCL-PPC-PCL Thermosetting coatings [152] Isocyanate free polyurethanes Thermosetting coatings [153] PPC Thermosetting coatings [154] TMCs Thermosetting coatings [155] Ethylene carbonate Thermosetting coatings [156] Nonisocyanate PC-PUs Thermosetting coatings [157] micelles as a model drug. The in vitro DOX release behaviors indicated that crosslinking of the micelle cores resulted in a slow drug release, and therefore, this process was significantly accelerated with adding glutathio...…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Cyclic carbonates were also introduced in polymer architectures as side‐chains as reported by Lex‐Balducci and co‐workers who copolymerized a cyclic carbonate methacrylate with oligo(ethylene glycol) methyl ether methacrylate and further studied gel polymer electrolyte obtained by swelling the accordingly obtained copolymers in a carbonate‐based electrolyte. [ 12,13 ] A noncyclic poly(propylene carbonate) providing an ionic conductivity of 10 −4 S cm −1 at ambient temperature was described by Zhang et al [ 14 ] Tominaga and co‐workers synthesized a noncyclic poly(ethylene carbonate) and further developed a hybrid membrane based on porous polyimide matrix, supporting a poly(ethylene carbonate)‐based SPE reaching an ionic conductivity of 10 −5 S cm −1 at 30 °C. [ 15,16 ] They also proved that the noncyclic poly(ethyne carbonate) could act as a suitable SPE, exhibiting high lithium transference number and high ionic conductivity that increases with the concentration of salts.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such difficulties, impregnated films are formed by filling ionic liquids or liquid electrolytes to enhance the ionic conductivity into the porous supports having excellent mechanical properties such as poly(vinylidene fluoride‐hexafluoropropylene) (PVdF‐HFP) . Alternatively, thermal as well as UV polymerizations between reactive monomers having notable ion‐conducting groups such as PEG and other monomers with mechanical properties similar to those of the derivatives (styrene monomers, in most cases) have been carried out to form copolymer films as gel electrolytes having both reasonable ionic conductivity and sufficiently good mechanical properties …”
Section: Introductionmentioning
confidence: 99%